Akankah Kualitas Dan Keradilan Pelayanan Dapat Menciptakan Kepuasan Dan Kepercayaan Pasien Rumah Sakit - Yassir; Abdul Haris (Jurnal Ekonomi, 2022)
Wahidin Hospital shows a growing occupancy rate, so it is interesting to study. The purpose of this study is to investigate the relationship between service quality and service fairness with patient satisfaction which has an impact on patient trust. The respondents of this study were hospital patients and the data were completely accurate and deserved to be analyzed as many as 100 questionnaires. Then the data were analyzed using WarpPLS. This study found that service quality can contribute significantly in encouraging patient satisfaction. Therefore, satisfaction will be obtained if the service obtained is good. Then, service fairness can explain significantly the increase in patient satisfaction. Thus, the satisfaction obtained by patients when getting good service justice. Furthermore, high patient satisfaction can generate patient confidence. Patients who feel good service and justice will feel satisfaction so that it has an impact on trust.